MINYAK ATSIRI JERUK KALAMANSI (Citrus microcarpa) SEBAGAI FORMULASI MASKER GEL (Peel-Off Mask) - Yuska Noviyanty; Hepiyansori Hepiyansori; Fransisca Epri Esaliya (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
The use of Citrus microcarpa essential oil is not widely known by the public. contains antioxidant compounds such as limonen and vitamin C. The dosage formulation is made in the form of Gel Mask (Peel-Off Mask) because Gel Mask (Peel-Off Mask) is a mask that is practical in its use, after drying the mask can be removed immediately and is able to remove the remnants of dirt that sticks to the surface of the facial skin. The process of making Gel Masks (Peel-Off Mask) of Kalamansi Orange Essential Oil (Citrus microcarpa) uses a variation of the concentration of Kalamansi Orange Essential Oil (Citrus microcarpa) 2%, 4%, 6%, the base used as Gelling Agent is PVA and HPMC, and evaluation of dosage includes organoleptic test, homogeneity test, dispersion test, dry time test, pH test, preference test or hedonic test. The results showed that Kalamansi Orange Essential Oil (Citrus microcarpa) can be made with a gel mask (Peel-Off Mask) and the difference in concentration can affect the physical properties of the Peel-Off Mask which includes the consistency and odor of the Gel Mask (Peel-Off Mask). Of the four formulas (F0, F1, F2, F3) the best preparation is F3 with a concentration of Kalamansi Orange Essential Oil (Citrus microcarpa) 6%.